Development of a Biosensor for Detection of Benzoic Acid Derivatives in Saccharomyces cerevisiae - Castaño-Cerezo, Sara; Fournié, Mathieu; Urban, Philippe; Faulon, Jean-Loup; Truan, Gilles (Frontiers in Bioengineering and Biotechnology, 2020)
4-hydroxybenzoic acid (pHBA) is an important industrial precursor of muconic acid and liquid crystal polymers whose production is based on the petrochemical industry. In order to decrease our dependency on fossil fuels and improve sustainability, microbial engineering is a particularly appealing approach to replace chemical synthesis. The optimisation of microbial strains, however, is still highly constrained by the screening stage. Biosensors have helped to alleviate this problem by decreasing the screening time as well as enabling higher throughput. In this paper, we constructed a synthetic biosensor, named sBAD, consisting of a fusion of the pHBA binding domain of HbaR from R. palustris, the LexA DNA binding domain at the N-terminus and the transactivation domain B112 at the C-terminus. The response of sBAD was tested in the presence of different benzoic acid derivatives, with cell fluorescence output measured via flow cytometry. The biosensor was found to be activated by the external addition of pHBA in the culture medium, in addition to other carboxylic acids including p-aminobenzoic acid (pABA), salicylic acid, anthranilic acid, aspirin and benzoic acid. Furthermore, we were able to show that this biosensor could detect the in vivo production of pHBA in a genetically modified strain. Good linearity was observed between the biosensor fluorescence and pHBA concentration. Thus, this biosensor would be well suited as a high throughput screening tool to produce, via metabolic engineering, benzoic acid derivatives.